3D modelling using solidworks : wall-mounted rainwater tank for stormwater detention in commercial areas - Foo, Swee Wen (Universiti Malaysia Sarawak (UNIMAS), 2017)
Rapid urban growth with increment of paved areas has resulted in increased stormwater runoff within built environments which could lead to flood events. Therefore, rainwater harvesting is one of the common approaches to store the stormwater temporarily to reduce the volume of runoff in dense urban areas. Normally, conventional rainwater harvesting tank has big capacity and it occupies large land spaces. In this project, a wall-mounted rainwater harvesting system is introduced for commercial buildings with limited empty spaces. Due to the large roof catchment area, three storage tanks are proposed to be installed on the building wall to achieve the desired storage capacity. With the aid of Solidworks Flow Simulation, the effectiveness of the wall-mounted rainwater harvesting system is investigated under various inlet designs (T-Inlet, L-Inlet, and Inclined-Inlet) subjected to three pipe sizes (60mm, 90mm and 120mm). It is found that Inclined-Inlet with 120mm pipe is the ideal design for such a system. It has the most balanced characteristics of smooth water flowing, and associated pressures for closed system. Velocities at tank outlets are with the least differences with 0.116m/s in Tank 1, 0.181m/s in Tank 2 and 0.308m/s in Tank 3. Meanwhile, the pressure within the three tanks also gives a close value about 102 kPa. Hence, a wall-mounted rainwater harvesting system is proven of its appropriate fluid dynamics and pressures to be integrated into commercial buildings for urban stormwater management.